Economic and ecological sustainability: The identity of opposites? - Bernhard Wieland (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2002)
It is often contended that there is a sharp conflict between the economist's and the ecologist's approach to the question of sustainability. This paper takes the opposite view. The paper attempts to show that both views can be formulated in a common analytical framework and that carried to its logical consequences the ecologic approach is a special case of the economic approach.
Keywords: 330; Nachhaltige Entwicklung; Umweltökonomik; Umwelt; Soziale Wohlfahrtsfunktion; Theorie